2019
DOI: 10.1155/2019/3708497
|View full text |Cite
|
Sign up to set email alerts
|

Naringin Reverses High-Cholesterol Diet-Induced Vascular Dysfunction and Oxidative Stress in Rats via Regulating LOX-1 and NADPH Oxidase Subunit Expression

Abstract: Hypercholesterolaemia is associated with oxidative stress and endothelial dysfunction and leads to the development of atherosclerosis. Naringin exhibits cardiovascular protective and antioxidant properties. Therefore, the aim of this study was to assess the effect of naringin administration on vascular oxidative stress and endothelial dysfunction in hypercholesterolaemic rats and to elucidate its underlying mechanism. Sprague Dawley rats were fed a diet with 1.5% cholesterol (HCD) for 8 weeks to induce hyperch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 46 publications
(67 reference statements)
2
30
0
Order By: Relevance
“…Further, western blot analysis revealed that there was a significant decrease in the expression of lectin‐like oxidized low‐density lipoprotein receptor‐1 (LOX‐1), NADPH oxidase subunits (p47phox, Nox2, and Nox4), iNOS, and oxidative damage markers in the aortic homogenate of naringin treatment animals. These results suggest the possible involvement of antioxidant activity, and down regulation of LOX‐1 and NADPH oxidase behind the protective effect of naringin in improving the endothelium dysfunction in hypercholesterolemic rats (Sirinat Pengnet et al, 2019).…”
Section: Discussionmentioning
confidence: 92%
“…Further, western blot analysis revealed that there was a significant decrease in the expression of lectin‐like oxidized low‐density lipoprotein receptor‐1 (LOX‐1), NADPH oxidase subunits (p47phox, Nox2, and Nox4), iNOS, and oxidative damage markers in the aortic homogenate of naringin treatment animals. These results suggest the possible involvement of antioxidant activity, and down regulation of LOX‐1 and NADPH oxidase behind the protective effect of naringin in improving the endothelium dysfunction in hypercholesterolemic rats (Sirinat Pengnet et al, 2019).…”
Section: Discussionmentioning
confidence: 92%
“…Endothelial dysfunction is substantially driven by reduced availability of NO as a consequence of increased oxidative stress, generation of free radicals, and other stress factors; polyphenols may improve the release of NO from the endothelial cells, leading to activation of cyclic guanosine monophosphate in vascular smooth muscle cells and exerting blood vessel relaxation, antioxidant, anti-inflammatory, and antithrombotic effects [ 64 ]. Flavonoids, such as anthocyanins [ 65 , 66 ], flavones (i.e., luteolin) [ 67 ], flavanones (i.e., naringin) [ 68 ], flavan-3-ols (i.e., epicatechin) [ 69 ], flavonols (i.e., kaempferol) [ 70 ] and isoflavones [ 71 ], and resveratrol [ 72 , 73 ] may play a direct role in improving the bioavailability in the bloodstream of NO by increasing the activation of inducible NO synthase (iNOS) and endothelial NO synthase (eNOS) provided by modulation of signal transduction, for instance through the phosphatidylinositol 3-kinase (PI3K)/Akt or the adenosine monophosphate-activated protein kinase (AMPK) pathways [ 67 ]. Together with other polyphenols, such as caffeic acid [ 74 ], kaempferol [ 75 ], quercetin [ 76 ], luteolin [ 77 ], and biochanin A [ 78 ], these compounds may exert vasorelaxing effects also by acting on vascular smooth muscle cells directly (through activation of BK channels or inhibition of Ca 2+ channels) or indirectly (through activation of Ca 2+ -activated K + channels in endothelial cells, leading to hyperpolarization and inhibition of Ca 2+ influx to vascular smooth muscle cells), eventually limiting construction and leading to vasorelaxation [ 79 ].…”
Section: Summary Of Potential Mechanisms Of Actionmentioning
confidence: 99%
“…Hypercholesterolemia is associated with oxidative stress and endothelial dysfunction and leads to the development of atherosclerosis. Pengnet et al ( 45 ) revealed that a reduction of aortic NO levels, increased of aortic superoxide ion levels, led to diminished vasodilatation. Moreover, they identified an increase of lectin-type oxidized LDL receptor (LOX)-1, NADPH oxidase subunits (p47phox, NOX2, and NOX4), and inducible NOS as well as 4-HNE expression in aortic tissues from hypercholesterolemic rats.…”
Section: Lipid Oxidation-derived Aldehydes In Cardiovascular Eventsmentioning
confidence: 99%